Endoscopic Submucosal Dissection for Gastric Tube Carcinoma after Esophagectomy Contributes to Long-Term Outcomes. (10th February 2022) - Hashimoto, Satoru; Sato, Hiroki; Mizuno, Ken-ichi; Takahashi, Kazuya; Takatsuna, Masafumi; Yokoyama, Junji; Ichikawa, Hiroshi; Takeuchi, Manabu; Kobayashi, Masaaki; Terai, Shuji
Abstract : The incidence of gastric tube carcinoma (GTC) after esophagectomy for esophageal carcinoma has increased in recent years. Surgical removal of the reconstructed gastric tube is associated with high mortality, and endoscopic submucosal dissection (ESD) is a promising alternative. There are limited reports of ESD for GTC. This study investigated the efficacy and safety of ESD in GTC. This single-center retrospective study examined patients who underwent ESD for GTC after esophagectomy at our institution between 2003 and 2018. The curability of GTC with ESD was evaluated histologically according to the Japanese Gastric Cancer Treatment Guidelines. Patient characteristics and procedural and long-term outcomes were analyzed. Overall, 31 patients (29 men and 2 women; median age, 73 years) with 45 GTC lesions underwent ESD. The mean period between primary esophagectomy and the diagnosis of GTC was 10.6 years. Bleeding during ESD was noted in two patients (6.5%). No other adverse or fatal events such as perforation were noted. Complete resection and curative resection were documented in 80.6% and 48.4% of cases, respectively. The 3-year and 5-year overall survival rates were 67.6% and 47.7%, respectively. The 3-year and 5-year disease-specific survival rates were 100% and 92.9%, respectively. One patient died of GTC, and fourteen patients died of other diseases, including primary carcinoma in five cases. ESD was safe and provided good long-term outcomes in patients with GTC. Regular long-term gastroscopy is required for the early detection of GTC. Patients with GTC after esophagectomy for esophageal carcinoma have a high risk of other primary carcinomas or comorbidities after ESD.